2005
DOI: 10.2987/8756-971x(2005)21[194:hposwn]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Host-Feeding Patterns of Suspected West Nile Virus Mosquito Vectors in Delaware, 2001–2002

Abstract: Paucity of data on host-feeding patterns and behavior of 43 mosquito species that are reported as suspected West Nile virus (WN) vectors has limited full evaluation of their vectorial capacity. Recent studies addressing this issue need additional confirmation and should also be expanded to include collections of species or subpopulations attracted to humans. We used 4 types of collection methods to collect mosquitoes, including omnidirectional Fay-Prince traps, Centers for Disease Control-type light traps, gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 14 publications
2
42
2
Order By: Relevance
“…These findings were consistent with prior host preference studies ( 8 , 9 , 16 , 20 ) and strongly support the view that this predominant "early season" species is most likely involved in initiation and amplification of WNV transmission among wild birds and rarely, if ever, feeds on humans in this region. This finding differs from a recent blood-meal analysis by Gingrich and Williams ( 19 ), who found that a limited number (n = 9) of Cx. restuans from Delaware were highly mammalophilic (9:1 mammal-to-bird ratio).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings were consistent with prior host preference studies ( 8 , 9 , 16 , 20 ) and strongly support the view that this predominant "early season" species is most likely involved in initiation and amplification of WNV transmission among wild birds and rarely, if ever, feeds on humans in this region. This finding differs from a recent blood-meal analysis by Gingrich and Williams ( 19 ), who found that a limited number (n = 9) of Cx. restuans from Delaware were highly mammalophilic (9:1 mammal-to-bird ratio).…”
Section: Discussioncontrasting
confidence: 99%
“…pipiens collected from suburban locales in nearby Westchester County, New York ( 9 ), but contrasts sharply with a recent study conducted in Delaware, where 69% of the blood meals taken by Cx. pipiens were from large mammals ( 19 ), which suggests a difference in host preference from more southern regions of its range.…”
Section: Discussionmentioning
confidence: 99%
“…Affinity for mammalian hosts, excluding humans in invasive Ae. albopictus has been reported from Hawaii (Tempelis et al 1970), temperate regions of North America (Savage et al 1993), United States (Niebylski et al 1994;Gingrich and Williams 2005;Richards et al 2006), and Spain (Munoz et al 2011). The results from the present study are at variance from these observations because only 34 % of the blood-fed Ae.…”
Section: Discussioncontrasting
confidence: 55%
“…Similarly, Cx. restuans fed upon avian hosts 62% of the time in this study, while it was reported to be exclusively ornithophilic in Connecticut (Molaei et al 2006) and highly mammalophilic in Delaware (Gingrich and Williams 2005). This level of variation may in part reflect the limited number of specimens analyzed in some of the previous studies (Apperson et al 2004, Gingrich andWilliams 2005).…”
Section: Discussionmentioning
confidence: 63%
“…restuans fed upon avian hosts 62% of the time in this study, while it was reported to be exclusively ornithophilic in Connecticut (Molaei et al 2006) and highly mammalophilic in Delaware (Gingrich and Williams 2005). This level of variation may in part reflect the limited number of specimens analyzed in some of the previous studies (Apperson et al 2004, Gingrich andWilliams 2005). However it is also possible that these data reflect the fact that host feeding choice may vary widely within a single species from location to location, which may in turn affect the role that each species plays both as an enzootic and as a bridge vector in different regions.…”
Section: Discussionmentioning
confidence: 63%